AMBARAN FUNGSI HATI PASIEN SKIZOFRENIA YANG MENGKONSUMSI RISPERIDONE DENGAN LORAZEPAM - Kurniati, Tripeni; Darmawan, Endang; Anggriani, Hesti (Indonesian Research Gateway, 2018)
Treatment with risperidone 1.5-6.0 mg/day provides good benefits for schizophrenia treatment, severe psychiatric disorder with long-term disability potential and limited availability of treatment options. According to the average percentage of patients with abnormal liver function tests, patients with clinically significant improvement (> 3 times of the normal upper limit for SGPT, aspartate aminotransferase.Abnormalities that are commonly without any symptom occur within 6 weeks of antipsychotic use (Correll et al., 2015). The purpose of this study is to analyze the liver function of schizophrenic in-patients who take risperidone and lorazepam in Amino Gondohutomo’s psychiatric hospital of Central of Java Province. The research subjects were 132 schizophrenic diagnosed patients who take risperidone and combination of risperidone and lorazepam. We used Chi Square Tests, Paried T Tests and One Sample Test.Based on the research results, it can be concluded that there is a correlation between readmisi and age group, in age group > 29 years more risk relapse than age group <29 years. Also, it can be concluded the combination of risperidone and lorazepam at risk 0,933 times will increase SGOT than get treatment with risperidone only and therapy the combination of risperidone and lorazepam at risk twice will increase SGPT rather than receive treatment with risperidone only.